Simultaneous readout of noncommuting collective spin observables beyond the standard quantum limit - Kunkel, Philipp; Prüfer, Maximilian; Lannig, Stefan; Rosa-Medina, Rodrigo; Bonnin, Alexis; Gärttner, Martin; Strobel, Helmut; Oberthaler, Markus K. (Physical review letters, 2019)
We augment the information extractable from a single absorption image of a spinor Bose-Einstein condensate by coupling to initially empty auxiliary hyperfine states. Performing unitary transformations in both the original and auxiliary hyperfine manifold enables the simultaneous measurement of multiple spin-1 observables. We apply this scheme to an elongated atomic cloud of 87Rb to simultaneously read out three orthogonal spin directions and with that directly access the spatial spin structure. The readout even allows the extraction of quantum correlations which we demonstrate by detecting spin-nematic squeezing without state tomography.
Gesehen am 28.04.2020